Lack of Gut Secretory Immunoglobulin A in Memory B-Cell Dysfunction-Associated Disorders: A Possible Gut-Spleen Axis - Carsetti, Rita; Di Sabatino, Antonio; Rosado, Maria Manuela; Cascioli, Simona; Piano Mortari, Eva; Milito, Cinzia; Grimsholm, Ola; Aranburu, Alaitz; Giorda, Ezio; Tinozzi, Francesco Paolo; Pulvirenti, Federica; Donato, Giuseppe; et al. (Frontiers in Immunology, 2020)
Background. B-1a B cells and gut secretory IgA (SIgA) are absent in asplenic mice. Human IgM memory B cells, which are functionally equivalent to mouse B-1a B cells are reduced after splenectomy. Objective. To demonstrate whether IgM memory B cells are necessary for generating IgA-secreting plasma cells in the human gut. Methods. We studied intestinal SIgA in two disorders sharing the IgM memory B cell defect, namely asplenia and common variable immune deficiency (CVID). Results. Splenectomy was associated with reduced circulating IgM memory B cells and disappearance of intestinal IgA-secreting plasma cells. CVID patients with reduced circulating IgM memory B cells had a reduced frequency of gut IgA+ plasma cells and a disrupted film of SIgA on epithelial cells. TLR9 and TACI induced in vitro IgM memory B cell differentiation into IgA+ plasma cells. TACI-expressing mucosal IgM memory B cells were localized under the epithelial cell layer where the TACI ligand APRIL was extremely abundant. Conclusions. Circulating IgM memory B cell depletion was associated with a defect of intestinal IgA-secreting plasma cells in asplenia and CVID. The observation that IgM memory B cells have a distinctive role in mucosal protection suggests the existence of a functional gut-spleen axis.